The Influence of Conflict Management on Organisational Performance: Evidence From Guinness Ghana Limited, Headquarters Accra, Ghana - Kelvin Mensah Ampomah; Oscar Agyemang Opoku; Godfred Osei Amankwah; Bashiru Atta Wahab (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2022)
The study set out to determine the influence of conflict management on the performance of Guinness Ghana Limited, Accra-Headquarters as an organisation. The study employed a quantitative research approach and descriptive survey and inferential statistics as the study design. The study was based on the views of 200 employees from the study institution with a self-administered questionnaire as the main research instrument. The study found that the higher the organization adopted negotiation, the more the performance increased, hence it helped improve the general working environment. It was also found that meditation has been used as a conflict management strategy and has proved to be an effective conflict management strategy. Finally, an effective arbitration channel was in place and it had a direct influence on the level of organizational performance. In the light of these findings, it was recommended that management should focus on increasing the utilisation of conflict management strategies such as negotiation, mediation and arbitration to increase organizational performance. In addition, the use of negotiation, mediation and arbitration as forms of conflict management strategy should be encouraged in resolving conflicts in the organization